Clinical experience after tetrafocal intraocular lens implantation “PANOPTIX” - Ibáñez-Hernández,Miguel Ángel (2020)
Abstract Purpose: To assess long, intermediate and near uncorrected visual acuity after a tetrafocal diffractive intraocular lens implantation, presence of dystopic phenomenon and patient satisfaction after surgery. Methods: Retrospective, observational study performed in Puerta de Hierro Specialties Hospital, in Jalisco, México. That included 100 eyes after phacoemulsification surgery by femtosecond assistance, followed by tetrafocal diffractive intraocular lens implantation due to cataract. Long, intermediate and near visual acuity without correction was measured, and presence or absence of dystopic phenomenon, plus patient satisfaction after surgery. Results: A total of 100 eyes in 50 patients who underwent cataract surgery with phacoemulsification by femtosecond assistance were evaluated. 100% underwent bilateral phacoemulsification. Long, intermediate, and near visual acuity after three months was in the most patients 20/20 (46%), 20/15 (44%) and Jaeger 1 (48%) respectively. The percentage or patients who refers halos was 7%; and other associated symptoms in 18%, being astenopia the most prevalent. The removal of the lens was not required in any case. Conclusion: Tetrafocal diffractive intraocular lenses provides excellent intermediate vision (at 60 centimeters) and satisfactory near (30 centimeters) and long (6 meters) visual acuity.